Physical Activity Increases Bone Mineral Density in Children with Type 1 Diabetes - Albane B.R. Maggio; René Rizzoli; Laetitia Marchand‐Martin; Serge Ferrari; Maurice Beghetti; Nathalie J. Farpour‐Lambert (2012)
Osteoporosis is a growing health problem in patients with type 1 diabetes mellitus (T1DM). The aim of this study was to determine the effects of a 9-month weight-bearing physical activity program on bone mineral density (BMD) and bone biomarkers in T1DM compared with healthy children.This was a randomized controlled trial including 27 diabetic and 32 healthy children (mean age = 10.5 ± 2.5 yr). Both T1DM and healthy participants were randomized to either an exercise or a control group (i.e., four groups). At baseline and 9 months, total body (TB), lumbar spine (LS2-LS4), femoral neck, and greater trochanter areal BMD (aBMD) and serum bone biomarkers (osteocalcin, type 1 collagen cross-linking) were measured. The intervention consisted of two 90-min sessions per week of weight-bearing physical activity (ball games, jumping, rope skipping, and gymnastics).Baseline variables were similar among groups. At 9 months, changes in TB (T1DM = 0.035 ± 0.022 g·cm(-2), healthy = 0.031 ± 0.017 g·cm(-2)) and LS2-LS4 (T1DM = 0.046 ± 0.038 g·cm(-2), healthy = 0.063 ± 0.034 g·cm(-2)) aBMD were statistically significant in the intervention groups and of similar magnitude between T1DM and healthy subjects. The level of type 1 collagen cross-linking (T1DM = -0.12 ± 0.32 ng·mL(-1), healthy = -0.36 ± 0.11 ng·mL(-1)) decreased in the intervention groups but was not associated with TB aBMD changes.Regular weight-bearing physical activity (180 min·wk(-1), including ball games, jumping activities, and gymnastics) improves total and LS2-LS4 bone mineral accretion in children with T1DM, in a similar magnitude to healthy subjects. We conclude that children with T1DM should be encouraged to practice regular physical activity to enhance peak bone mass and prevent osteoporosis later in life.